2022
DOI: 10.54386/jam.v24i1.1002
|View full text |Cite
|
Sign up to set email alerts
|

Wheat yield prediction based on weather parameters using multiple linear, neural network and penalised regression models

Abstract: Wheat yield production is largely attributed by weather parameters. Model developed by multiple linear, neural network and penalised regression techniques using weather data have the potential to provide reliable, timely and cost-effective prediction of wheat yield. Wheat yield data and weather parameter during crop growing period (46th to 15th SMW) for more than 30 years were collected for study area and model was developed using stepwise multiple linear regression (SMLR), principal component analysis (PCA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…As shown in Table 6, D index value of SPSS is close to 1 (0.99) whereas that of ANN (0.1 to 0.4) and ARIMA (0.3) which is nowhere close to 1, this clearly indicated that the performance of SPSS model was far better than ANN and ARIMA model to predict mustard yield for Udaipur region. [13] also conducted study on the performance evaluation for wheat yield prediction using PCA-stepwise multiple linear regression (SMLR), ANN and other techniques. The results showed that out of five regions of study area, in three regions (Ludhiana, Amritsar and IARI-New Delhi) the prediction of wheat using ANN during validation showed comparatively more error due to over fitting than validation results using SPSS.…”
Section: Performance Evaluation Of Models Using Different Error Indicesmentioning
confidence: 99%
“…As shown in Table 6, D index value of SPSS is close to 1 (0.99) whereas that of ANN (0.1 to 0.4) and ARIMA (0.3) which is nowhere close to 1, this clearly indicated that the performance of SPSS model was far better than ANN and ARIMA model to predict mustard yield for Udaipur region. [13] also conducted study on the performance evaluation for wheat yield prediction using PCA-stepwise multiple linear regression (SMLR), ANN and other techniques. The results showed that out of five regions of study area, in three regions (Ludhiana, Amritsar and IARI-New Delhi) the prediction of wheat using ANN during validation showed comparatively more error due to over fitting than validation results using SPSS.…”
Section: Performance Evaluation Of Models Using Different Error Indicesmentioning
confidence: 99%
“…Weights are taken as correlation coefficients between yield and weather variables in respective periods. In the same way, indices were also produced for interaction of weather variables by using weekly products of weather variables taking two at a time (Aravind et al, 2022).…”
Section: Data Collectionmentioning
confidence: 99%
“…Tibshirani (1996) proposed LASSO, which can be utilized in the crop yield forecasting technique. Aravind et al (2022) reported that elastic Net and LASSO were found to be the best model followed by PCA-SMLR, SMLR, PCA-ANN and ANN respectively for wheat yield prediction of different locations of north-west India. Support vector machine is a classification and regression prediction tool that uses machine learning theory to maximize predictive accuracy while automatically avoiding over-fitting to the data.…”
mentioning
confidence: 99%
“…But it consumes a lot of time and needs more human effort. The other alternate of this traditional method is the crop yield estimation by models developed using various statistical techniques.In the current scenario, forecasting of crop yield using Artificial Neural Network (ANN), Least Absolute Shrinkage and Selection Operator (LASSO) and Elastic Net (ELNET) getting a great deal of attention (Das et al, 2020, Aravind et al, 2022. Various efforts have been made by the researchers to develop preharvest yield forecast models based on yield and weather-datasets.…”
mentioning
confidence: 99%
“…In the current scenario, forecasting of crop yield using Artificial Neural Network (ANN), Least Absolute Shrinkage and Selection Operator (LASSO) and Elastic Net (ELNET) getting a great deal of attention (Das et al, 2020, Aravind et al, 2022. Various efforts have been made by the researchers to develop preharvest yield forecast models based on yield and weather-datasets.…”
mentioning
confidence: 99%